Filling up in the city: The typological evolution of service and petrol stations in Antwerp, 1945-1975 (Bulletin KNOB, 2023)
The global automotive industry has undergone major developments in the last decade, perhaps the most decisive transformations in its one hundred-year existence. The current fundamental transition from a fossil fuel-driven motor to an electric power source heralds the end of an era. This revolutionary change is perhaps a good time to reflect upon the past one hundred years of fossil-fuel powered driving and in particular on its very distinctive service architecture. This article provides insight into the evolution from kerbside pump to self-service petrol station within the greater Antwerp area of Belgium in the period 1945 to 1975. It is a condensed version of an architectural-historical research project based on over two hundred building and environmental permits held in the Antwerp City Archives and involving the close study and analysis of a set of parameters. The outcome of this research served as the basis for conclusions about developments in the design of post-war service stations seen in relation to the socio-economic situation and the evolving spatial design of the city of Antwerp. In situ research into the current state of those buildings or locations resulted in an inventory of surviving examples of this built heritage which could serve as basis for further revaluation and, ultimately, protection of part of this built heritage.